Electronic Correspondence Management Application Design - Kanyarat Jitsaeng (Yayasan Gema Bina Nusantara, 2023)
The aim of this research is to find out how to implement and optimize the electronic correspondence management application for all employees. Data collection in this research used literature study methods, field studies, observations, and interviews. In the method used for this research, the author uses the phases contained in the FAST methodology (framework for the application of systems thinking). Based on the results of this research, it was found that designing an electronic correspondence management application can be done using the system development methodology proposed by FAST (Framework Application of System Thinking) using 7 phases out of the 8 phases contained in FAST. The phases used are: definition scope, problem analysis, requirements analysis, logical design, physical design, construction, and implementation. In terms of building this electronic correspondence management application, the implementation process or writing code can use the PHP and MySQL programming languages.